Real-time water quality measurements and predictions for the Marina Catchment - Lee, Maureen Seok Mui. (2009)
The objectives of the project are to establish a relationship between real-time and lab-measured data and using this correlation to predict real time water quality in the Marina Catchment. The YSI was used in monitoring real-time water quality while the auto-sampler triggered during a heavy storm collects water samples to be tested in the laboratory. A high correlation value between YSI-measured turbidity and lab-measured TSS was found and thus prediction of TSS concentration was done, given the turbidity value. Loading of the river was thus estimated. Some of the problems faced during the project were the lack of rainfall and instrument errors, resulting in limited data collected. Despite the limitations and problems faced, the correlation found could be used in future predictions. Continuous sampling could be done to validate the accuracy of the relationship.